THE EFFECT OF USING CERAMIC WASTE POWDER AS A SUBTITUTE FOR CEMENT ON THE COMPRESSIVE STRENGTH OF K250 CONCRETE - Samsul Arif; Dwi Kartikasari (U Karst, 2020)
In every construction work, you will find the remains of building materials no longer used and disposed of as waste, one of which is a ceramic waste. Ceramic waste is waste that has no selling value. Therefore the authors in this study will utilize ceramic waste as a substitute for cement with concrete quality K250. Several studies have also explained that ceramic waste contains silica, which has high adhesion, making it suitable as a substitute for cement. The process of mixing ceramic waste as a K250 quality concrete mixture is carried out according to the Indonesian SNI Standard and ASTM standards by laboratory testing using a variation of 3%, 4%, and 5% as a substitute cement. From these results, the composition of the addition of 3% ceramic waste has an average compressive strength of 330.99 kg/cm2, a composition of 4% has an average compressive strength value of 243.88 kg/cm2, and a percentage of 5% has an average compressive strength value 258.41 kg/cm2. The more the ceramic waste mixture as a substitute for cement, the lower the compressive strength of the concrete